Use of Information and Communications Technology as a pedagogical asset in times of crisis - Avendaño Castro, William Rodrigo; Hernández S., César A.; Prada Núñez, Raúl (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: The purpose of this paper is to describe the use of Information and communications technology as a pedagogical asset in times of crisis. Originality: it deals with the use of ICT during COVID-19 pandemic, which conditions certain uses and where pedagogy is understood as an interactive teaching process in higher education. Method: this is a quantitative, non-experimental, cross-sectional and descriptive research. Strategies / information gathering: the strategies are divided into three phases: 1) research design, 2) data collection, and 3) analysis and development.  Descriptive statistics were applied to the data obtained from an online questionnaire answered by 226 participants from the Universidad Francisco de Paula Santander. Conclusions: this research shows the importance of the pedagogical component in the use of ICT as a key factor for the introduction of remote teaching and the advancement of technology-mediated learning processes.